Quantitative comparison of mobility and gross motor function in Brazilian children with cerebral palsy - de Mello Monteiro, Carlos B.; Araujo, Daniele Z.; Silva, Talita D.; Pulz, Cristiane; Prumes, Marcelo; Abreu, Luiz Carlos de [UNESP]; Valenti, Vitor Engrácia [UNESP]; Adami, Fernando; de Carvalho, Tatiana Dias; Rossi, Renata C.; Vanderlei, Franciele M.; Malheiros, Silvia R. P. (Drunpp-sarajevo, 2012)
Background: Cerebral palsy (CP) presents changes in posture and movement as a core characteristic, which requires therapeutic monitoring during the habilitation or rehabilitation of children. Besides clinical treatment, it is fundamental that professionals use systems of evaluation to quantify the difficulties presented to the individual and assist in the organization of a therapeutic program. The aim of this study was to quantitatively verify the performance of children with spastic di-paresia type CP.Methods: The Pediatric Evaluation of Disability Inventory (PEDI) and Gross Motor Function Classification System (GMFM) tests were used and classification made through the GMFCS in the assessment of 7 patients with CP, 4 females and 3 males, average age of 9 years old.Results: According to GMFCS scales, 17% (n=1) were level II and 83% (n=6) were level III. The PEDI test and 88 GMFM items were used in the area of mobility. We observed that there was high correlation between mobility and gross motor function with Pearson's correlation coefficient =0.929) showing the likely impact of these areas in the functional skills and the quality of life of these patients.Conclusion: We suggest the impact of the limitation of the areas in functional skills and quality of life of these patients.
Keywords: Cerebral Palsy; Activities of daily living; Mobility Limitation